Effectiveness of the Strength-based Intervention on Subjective Well-being and Psychological Capital in Female Students With the Oppositional Defiant Disorder - Mohsen Ghorbani; Fatemeh Talebi; Elahe Khodadadi; Fatemeh Sadat Mohtashami; Sahar Froumandi (Gonabad University of Medical Sciences, 2023)
Background: It is important to recognize and use the strengths of children with oppositional defiant disorder (ODD). This study assessed whether strength-based intervention is effective on subjective well-being and psychological capital in children with ODD. Methods: This research was a quasi-experimental study with a pre-test and post-test design with a control group. The statistical population included 30 students with ODD in discreet six, which were selected through multi-stage clustering in Tehran during the academic year 2022. Then, the individuals were randomly assigned to the experimental and control groups (each group: n=15). The subjective well-being and Luthans' psychological capital (PCQ) questionnaires were administered. For the experimental group, a strength-based intervention was administered in eight sessions of 75 minutes per week, while the control group received no treatment. The data were analyzed using MANOVA and SPSS software, version 26. Results: The strength-based intervention had positive effects on subjective well-being (F1, 28=23.42, P<0.001) and psychological capital (F1, 28=28.12, P<0.001) in children with ODD. Conclusion: This type of approach builds on clients' strengths, seeing them as resourceful and resilient when they are in adverse conditions. This study encourages new evidence for the efficacy of a strength-based intervention.